2018
DOI: 10.1016/j.microrel.2018.06.047
|View full text |Cite
|
Sign up to set email alerts
|

V subthreshold hysteresis technology and temperature dependence in commercial 4H-SiC MOSFETs

Abstract: V TH subthreshold hysteresis measured in commercially available 4H-SiC MOSFET is more pronounced in trench than in planar ones. All planar devices from different manufacturers exhibit an inverse temperature dependence, with the hysteresis amplitude reducing as the temperature increases, whereas all trench devices from different manufacturers exhibit the opposite behaviour. A physical interpretation is proposed, based on experimental evidence, which demonstrates that temperature dependence of the V TH subthresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Some of the difficulties that prevent WBG devices from becoming mainstream are related to concerns such as reliability and specific driver needs. The reliability of SiC MOSFETs is actually plagued by NBTI [1,[4][5][6][7][8] caused mainly by hole trapping in the oxide [2]. This phenomenon affects the operation of the device by shifting its V TH either permanently or in a recoverable manner.…”
Section: • Lower Ronmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the difficulties that prevent WBG devices from becoming mainstream are related to concerns such as reliability and specific driver needs. The reliability of SiC MOSFETs is actually plagued by NBTI [1,[4][5][6][7][8] caused mainly by hole trapping in the oxide [2]. This phenomenon affects the operation of the device by shifting its V TH either permanently or in a recoverable manner.…”
Section: • Lower Ronmentioning
confidence: 99%
“…It has been observed that the drain leakage current SiC MOSFETs depends on the OFF-state voltage applied on the gate [1,3]. When a negative gate bias is applied for a short time in the OFF-state, the drain current leakage is enhanced for as long as the applied bias is kept under the threshold voltage.…”
Section: A What Is the Vth Subthreshold Hysteresis?mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations have targeted a benchmark of commercially available devices, based in particular on differences in their gate terminal technology [11]. For illustration, Fig.…”
mentioning
confidence: 99%